2018
DOI: 10.1016/j.cell.2018.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Genetic Adaptations to Diving in Sea Nomads

Abstract: Understanding the physiology and genetics of human hypoxia tolerance has important medical implications, but this phenomenon has thus far only been investigated in high-altitude human populations. Another system, yet to be explored, is humans who engage in breath-hold diving. The indigenous Bajau people ("Sea Nomads") of Southeast Asia live a subsistence lifestyle based on breath-hold diving and are renowned for their extraordinary breath-holding abilities. However, it is unknown whether this has a genetic bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 77 publications
(104 reference statements)
10
122
0
2
Order By: Relevance
“…In addition, although 2% to 3% of the total RBC mass is located in the spleen, this can increase with increasing spleen size and can be responsible for refractoriness to RBC transfusion . Finally, supporting the notion that RBCs can be sequestered and released when necessary, animals and humans have a diving and exercise response, which consists of contraction of the spleen and release of RBCs into the circulation in response to these stresses . If the phenomenon of temporary retention of transfused RBCs does occur regularly, this would have significant implications for calculating the PTR results used for FDA approval and licensure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although 2% to 3% of the total RBC mass is located in the spleen, this can increase with increasing spleen size and can be responsible for refractoriness to RBC transfusion . Finally, supporting the notion that RBCs can be sequestered and released when necessary, animals and humans have a diving and exercise response, which consists of contraction of the spleen and release of RBCs into the circulation in response to these stresses . If the phenomenon of temporary retention of transfused RBCs does occur regularly, this would have significant implications for calculating the PTR results used for FDA approval and licensure.…”
Section: Discussionmentioning
confidence: 99%
“…However, 31 outside of certain contexts such as experimental evolution of viruses or bacteria [3][4][5][6] or analyses of 32 ancient DNA samples [7,8], in most cases such direct observations of allele frequencies at multiple 33 points in the history of a population are unavailable. Instead, selection must be inferred from 34 contemporary, modern data. A wide variety of methods have been developed to detect selection 35 based on patterns observed from modern DNA sequences (e.g.…”
Section: Introduction 29mentioning
confidence: 99%
“…One advantage over the composite likelihood approach is that 89 ABC can capture dependencies between linked neutral sites. For example, methods have been 90 used to jointly infer the strength and timing of selection acting on a locus and determine whether 91 a sweep occurred from a de novo vs standing variant [32][33][34][35]. However, a major disadvantage of 92 such approaches is that the amount of simulation necessary to obtain an accurate estimate grows 93 dramatically with the dimensionality of the observed data (for a discussion, see e.g.…”
Section: Introduction 29mentioning
confidence: 99%
“…Classic examples include cultures that practice cattle herding being associated with increased frequency of the allele associated with the ability to digest milk sugar throughout adulthood (lactase persistence) [12], and cultures that practice cereal agriculture being associated with greater copy numbers of a gene that promotes the ability to digest dietary starch [13]. It has also recently been shown that the Bajou people of Southeast Asia who practice a unique form of fishing through breath hold diving also have increased frequencies of genes associated with large spleens that act as a reservoir of oxygenated red blood cells [14]. These examples involve a feedback mechanism where the cultural behaviour selects for the increase in a specific gene variant that in turn better enables the cultural behaviour [10], and the effects are therefore localised to specific sites in the genome.…”
Section: Introductionmentioning
confidence: 99%